2004
DOI: 10.1103/physrevb.69.014409
|View full text |Cite
|
Sign up to set email alerts
|

Quantum form of the double-exchange interaction

Abstract: A quantum form of the Hamiltonian for a double-exchange ͑DE͒ system, based on the results of Anderson and Hasegawa's semiclassical treatment, is presented together with several predictions. The magnetization decreases mainly in 3/2 and 5/2 powers of temperature at low temperature but includes a T 3 term. The Curie temperature, in a rescaled DE coupling energy (ͱ2b/2S 2 )J d unit, is dependent on hole concentration x and has highest value that is about 1/3 that of ordinary Heisenberg magnet at xϭ0.5. The suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Our T c s are in approximate coincidence with the experimental values [13]. Especially, for La 0.67 Ca 0.33 MnO 3 , our T c = 286 K approximately agrees with the experimental values T c = 250 K [10] and 260 K [13], but disagrees with T c = 1050 K which is calculated from the quantum DE theory [8]. If the quantum DE theory includes the lattice distortion effect [9], band-structure calculations lead to T c = 270 K [8].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Our T c s are in approximate coincidence with the experimental values [13]. Especially, for La 0.67 Ca 0.33 MnO 3 , our T c = 286 K approximately agrees with the experimental values T c = 250 K [10] and 260 K [13], but disagrees with T c = 1050 K which is calculated from the quantum DE theory [8]. If the quantum DE theory includes the lattice distortion effect [9], band-structure calculations lead to T c = 270 K [8].…”
Section: Discussionsupporting
confidence: 66%
“…lattice effect, as pointed out by Millis et al [9]. Since the lattice degree of freedom does not need to be added to explain CMR, the Curie temperature T c obtained from the semiclassical [5] and quantum [8] treatment is much higher than the experimental T c [9,10].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…More and more evidence has indicated that the DE model alone is not sufficient to explain the CMR effect. For example, if we take only the DE interaction into account, the value of the Curie temperature (T c ) for R 1-x M x MnO 3 (R = La, Nd, Pr and M = Sr, Ca, Ba) is theoretically expected to reach a maximum at x = 0.5 [5], rather than around x = 0.33. Furthermore, the theoretical value of T c is much higher than the experimental one.…”
Section: Introductionmentioning
confidence: 97%
“…Previously, we developed a quantum form Hamiltonian for the double exchange (DE) interaction and showed that quantum localized spins appear in a linear form of the scalar product in the Hamiltonian that can be treated in a way similar to a pure Heisenberg magnet. 2 Second, as De Gennes 3 pointed out, in hole-doped manganites the DE interaction will compete with antiferromagnetic superexchange (SE). The latter can be written in a typical Heisenberg form.…”
Section: Introductionmentioning
confidence: 99%